Reasons for Failure of Information Technology and Information System Related Human Resource Project Implementations in a GLC- A Case Study - Purushothaman, Sangari (2014)
Information Technology (IT) and Information System (IS) has become an essential part of all business functions. Consequently, the involvement of IT and IS in Human Resource Management (HR) is intensifying. HR is becoming a more technology-based function and HR technology trend is also changing radically from year to year. However, the IT and IS project failure rates are also rather apparent. Globally, the failure rate of IT and IS project is high and is expected to increase in the coming years. GLCs invest a huge sum of money and resources on IT and IS related HR projects which typically does not achieve the actual planned objectives resulting in a great loss to the organization. This study therefore aimed to investigate the reasons for IT and IS related HR project implementations in a GLC. The factors examined include technical complexity, quality of human resource and capabilities, lack of project management skills and inadequate change management initiatives. Questionnaires were distributed to the project team members in the GLC. The research revealed that technical complexity, poor cross-functional coordination, lack of project management skills and lack of management support and commitment are the factors contributing towards the failure of IT and IS related HR Project Implementations in the organization. Additionally, technical complexity appears to be the most dominant factor leading to the failure of IT and IS related HR Project Implementations in the organization. The study was then concluded with recommendations directed towards the management team, project teams and the Human Resource department of the organization.